2012
DOI: 10.5455/bcp.20111212084626
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic Malignant Syndrome Due to Risperidone Overdose in a Child: A Case Report

Abstract: Bir çocukta risperidon aşırı dozuna bağlı gelişen nöroleptik malign sendrom: Bir olgu sunumu Nöroleptik malign sendrom, nadir görülen ancak ölümcül olabilen, antipsikotik ilaçlara karşı gelişen idiosenkrazik bir reaksiyondur. Bu sendrom hipertermi, kas rijiditesi, akinezi, şuur değişikliği, otonomik disfonksiyon, yüksek kreatinin kinaz seviyesi, lökositoz ile karakterizedir. Bu yazıda, risperidona bağlı nöroleptik malign sendrom gelişen, 2,5 yaşındaki erkek olgu, literatürdeki en küçük olgu olması nedeniyle su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The results showed that increased CPK level in all cases of severe and fatal toxicity grades and in (12 %) of cases of moderate grade. This is in agreement with Saltik and Basgul, (2012) who reported that numerous cases of Neuro Malignant Syndrome (NMS) have been reported with atypical antipsychotic medications including clozapine, olanzapine, quetiapine, and risperidone in recent years. On contrary to Strawn et al, (2007) ; Seitz and Gill, (2009) reported that NMS most often associated with typical high-potency neuroleptics e.g.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that increased CPK level in all cases of severe and fatal toxicity grades and in (12 %) of cases of moderate grade. This is in agreement with Saltik and Basgul, (2012) who reported that numerous cases of Neuro Malignant Syndrome (NMS) have been reported with atypical antipsychotic medications including clozapine, olanzapine, quetiapine, and risperidone in recent years. On contrary to Strawn et al, (2007) ; Seitz and Gill, (2009) reported that NMS most often associated with typical high-potency neuroleptics e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Concurrently with proteolysis, other processes occur such as fibrinolysis and coagulation. [ 13 ] The latter is associated with nonspecific resistance of the body.…”
Section: Introductionmentioning
confidence: 99%